2023
DOI: 10.26434/chemrxiv-2023-l8q0t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Silver(I)-Catalyzed Synthesis of Cuneanes from Cubanes and their Investigation as Isosteres

Abstract: Bridged or caged polycyclic hydrocarbons have rigid structures that project substituents into precise regions of 3D space, making them attractive as linking groups in materials science and as building blocks for medicinal chemistry. The efficient synthesis of new or underexplored classes of such compounds is therefore an important objective. Herein, we describe the silver(I)-catalyzed rearrangement of 1,4-disubstituted cubanes to cuneanes, which are strained hydrocarbons that have not received much attention f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…While the 1,3-disubstituted cuneanes (1,3-cuneanes) have been described as early as 1970 by Eaton and co-workers [69] their selective synthesis had not been studied until recently [70]. Selected exit vector parameters showed that substituent distance d and scaffold carbon distance r of 1,3-cuneanes closely resemble the distances found at meta-benzene (Figure 26) [70][71][72]. While the substituent angle φ 1 of 1,3-cuneanes is only slightly larger than in metabenzene, the dihedral angle θ is significantly larger and strongly dependent on the specific substituents.…”
Section: 3-disubstituted Cuneanesmentioning
confidence: 95%
See 2 more Smart Citations
“…While the 1,3-disubstituted cuneanes (1,3-cuneanes) have been described as early as 1970 by Eaton and co-workers [69] their selective synthesis had not been studied until recently [70]. Selected exit vector parameters showed that substituent distance d and scaffold carbon distance r of 1,3-cuneanes closely resemble the distances found at meta-benzene (Figure 26) [70][71][72]. While the substituent angle φ 1 of 1,3-cuneanes is only slightly larger than in metabenzene, the dihedral angle θ is significantly larger and strongly dependent on the specific substituents.…”
Section: 3-disubstituted Cuneanesmentioning
confidence: 95%
“…1,3-Cuneanes can be obtained by metal-induced isomerisation of 1,4-cubanes [69]. Recent reports of their synthesis indicate that silver salts enable the isomerisation to occur efficiently (Scheme 18A) [70][71][72]. Experimental results and computational investigations by Stephenson and co-workers showed that the obtained ratio of 1,3-cunanes to 2,6-cuneanes is dependent on the cubane substituents [71].…”
Section: 3-disubstituted Cuneanesmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] For further discussions, exit vector parameter (EVP)based method was used, [43,44] which had been applied by our group for analysis of various cyclic systems previously [45][46][47][48][49][50][51] and is being adopted by a wider chemical community. [25,27,[52][53][54] The basic idea of this approach is simulating the functional groups mounted onto the scaffold by two exit vectors. Carbon atoms of the (bi)cyclic ring system bearing the functional groups are used as the starting points of these vectors, whereas the direction is defined by the attached bonds (Figure 2, A).…”
Section: Entrymentioning
confidence: 99%
“…When a 1,6disubstituted cubane is used as the substrate, two products, Prod1 and Prod2, can be generated depending on the metal, ligand, and counteranion employed. In 2023, Lam, 34 Nagasawa, 35 and Stephenson 36 reported new progress on this reaction nearly at the same time. In Lam's report, a mild strategy using AgNTf 2 as the catalyst selectively yielded Prod1 at room temperature with dichloromethane (DCM) as the solvent (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%